Assessing the inter- & intra-reliability of a customised volleyball performance analysis system to analyse complexes and the efficacy of the associated skills - Steven Nicklin; Lee Nelson; Evelyn Carnegie; Jayamini Ranaweera; Greg Doncaster (PLoS ONE, 2025)
Within volleyball, performance analysis is employed to identify key performance indicators (KPIs) in relation to success. To date, however, despite the growth in performance analysis, there is little appreciation of the assessment, importance and reporting of reliability of individual variables. This study seeks to establish the inter- and intra-reliability of a bespoke notational analysis system designed for assessing volleyball performance, considering complexes, position, skill, type of skill, and skill efficacy. To establish the inter-reliability, two coders analysed 9 matches, randomly selected from a pool of elite international matches. In addition, to establish the intra-reliability, the primary coder re-analysed one match per month over a nine-month data collection period. Cohen’s Kappa (κ) were established for nominal data, whilst the values for skill efficacy were reported as a Weighted Kappa alongside an Inter-Class Correlation (ICC). Kappa and Weighted Kappa values for all data were shown to be above the acceptable thresholds (κ = 0.75, κ = 0.60, respectively). The present study demonstrates that it is plausible for a bespoke volleyball coding system, implementing a wide array of variables, to have high levels of inter- and intra-reliability. Findings highlight that it is possible for such a system to be utilised over a prolonged period of data collection.